Mortality of Spanish former elite soccer players and coaches - Diz, J. C.; Sueiro, S. I.; Ferreira, E. D.; Sanchez-Lastra, M. A.; Ayán, C. (International Journal of Sports Medicine, 2021)
We analyzed whether male Spanish elite soccer players live longer than the general population. Secondly, we compared their mortality with a cohort of soccer players who continued working as soccer elite coaches after retirement. Using age and calendar-date adjusted life tables, we analyzed the mortality hazard ratio of 1333 Spanish male players born before 1950, and who played in elite leagues from 1939, compared with the Spanish population. Using Cox proportional hazards model we compared their mortality with a cohort of 413 players who continued as coaches. Players showed significantly lower mortality than the general population, but this advantage decreased with advanced age, disappearing after 80 years. Coaches showed a similar pattern. Comparing players versus coaches, date of birth and years as professional were associated with survival, but debut age and player position were not. Unadjusted median survival time was 79.81 years (IQR 72.37-85.19) for players and 81.8 years (IQR 74.55-86.73) for coaches. Kaplan-Meier estimator adjusted for covariables showed no difference between cohorts (p=0.254). In conclusion, former Spanish male players showed lower mortality than the general population, but this effect disappeared after 80 years of age. Continuing their career as coaches after retirement from playing did not confer major benefits.